Implementasi Metode Logika Fuzzy Simple Additive Weighting (Saw) Dalam Pencarian Rumah Kos Terbaik Di Sekitar Universitas Mataram Berbasis Website - Baiq Nurul Aini; Ida Bagus Ketut Widiartha; Royana Afwani (Journal of Computer Science and Informatics Engineering (J-Cosine), 2017)
Abstract - Searching for boarding house become harder because of the little number of media provide information about it. So that, this research is presented in order to provide information about boarding house . This research is about system that use to search the best boarding house around university of mataram using Simple Additive Weighting (SAW) as deciding support system. SAW is a method that count up based on a certain integrity. The accounting system that SAW does based on criteria that already decided. Based on data collection had done, it is found that the criteria to search a boarding house such as facility, cost, and distance with criteria based on value of priority from the most important are cost, distance and facility. Web-based implementation of fuzzy logic with Simple Additive Weighting (SAW) method for searching best boarding house around Mataram University had done, it can give 10 best boarding house alternative Which has adjusted with criteria that users wanted. Each function in Website has already run with Black Box as examining system method. Moreover, to examine the user’s satisfaction MOS is used, and it is gained value higher that 4 with good value indicates that respondent agree with application which already made. Keywords: Boarding House, Criteria, Alternative, SAW Method, Black Box, MOS